1996
DOI: 10.1183/09031936.96.09112236
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD44 and integrins in bronchial mucosa of normal and mildly asthmatic subjects

Abstract: E Ex xp pr re es ss si io on n o of f C CD D4 44 4 a an nd d i in nt te eg gr ri in ns s i in n b br ro on nc ch hi ia al l m mu uc co os sa a o of f n no or rm ma al l a an nd d m mi il ld dl ly y a as st th hm ma at ti ic c s su ub bj je ec ct ts s Significantly increased numbers of eosinophils (p<0.01) were evident in the bronchial submucosa of asthmatic subjects. In epithelium there were more CD44+ (p<0.02) and lymphocyte function-associated antigen-1 (LFA-1)+ (p<0.06) leucocytes in asthmatics than in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Within this network, CD44 encoding a cell surface adhesion receptor was the most highly ranked hub gene (degree = 59). A previous study showed that CD44 was significantly up-regulated in the bronchial epithelium in asthmatics compared with the controls [42]. Higher expression of CD44 in blood eosinophils could regulate the recruitment and function of leukocytes in asthmatics and are considered as a marker of bronchial asthma [43].…”
Section: Resultsmentioning
confidence: 99%
“…Within this network, CD44 encoding a cell surface adhesion receptor was the most highly ranked hub gene (degree = 59). A previous study showed that CD44 was significantly up-regulated in the bronchial epithelium in asthmatics compared with the controls [42]. Higher expression of CD44 in blood eosinophils could regulate the recruitment and function of leukocytes in asthmatics and are considered as a marker of bronchial asthma [43].…”
Section: Resultsmentioning
confidence: 99%
“…What pointed toward layilin as an ideal HA receptor to be involved epithelial permeability is that it is known to interact with members of the ezrin, radixin, and moesin proteins (81) that are key regulators of cytoskeletonplasma membrane interactions in polarized cell. CD44 and RHAMM are two of the better characterized HA receptors in airway epithelial cells (19,21,(82)(83)(84), but in intact epithelium CD44 expression is restricted to the basolateral domain (83,85,86) and thus, at least initially, cannot be accessed by fragments released during luminal HA degradation. RHAMM is apically expressed (19,21) but lacks a cytoplasmic domain.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent repair mechanisms are also implicated in airway remodeling [ 40 , 41 ]. These include upregulation of cyclin-dependent kinase inhibitor, p21 (waf) [ 42 ], EGFR [ 43 ] and CD-44 [ 44 , 45 ]. In asthma, epithelial shedding is largely attributed to the induction of apoptosis in AECs by infiltrating T cells and eosinophils along with increased pro-inflammatory cytokines including IFN-gamma and TNF-alpha [ 46 ].…”
Section: Discussionmentioning
confidence: 99%